Institutional changes and the Shifting Power Network: Planning Wusong Port from 1898 to 1999 - Jiang, Hao; Hou, Li (International Planning History Society Proceedings, 2018)
In this paper, the authors introduce the issue of institution as a factor of considerable significance. Based on field investigation and historical geography analysis, inquiring port plans, policy documents, laws and regulations as the basic historical data, the authors try to review the process of developing Wusong Port in the twentieth century and analyse the dynamic mechanism of its evolution from the perspective of institutional changes. The first section of this paper provides an overview of the development trajectory of Wusong Port, which focuses on its functions and locations changes. The second section briefly discusses the shifting power network that had historically governed the port and analyses relationship between the port and the city. The impact of administrative zoning adjustment is particularly mentioned, since the changes of the function of Wusong port were always accompanied by it. The third section explores the planning of the Wusong port in different historical periods. This article provides evidence that government-led port exploitation plays a great role in the fundamental change of Wusong Port – from a naval port, to a commercial port, to an industrial port, and finally an international cruise port.